Role of Nanotechnology in Plant Fungal Diseases: An Emerging Need to Control Fungal Diseases (Journal of Agriculture and Biology, 2024)
Fungal diseases significantly impact crop production, causing considerable economic losses and environmental harm. Nanotechnology, particularly nanoparticles (NPs) has emerged as a pivotal tool for advanced pathogen diagnostics and management, exhibiting novel antifungal properties such as cell damage, liquid peroxidation and DNA destruction. This review highlights specific NPs (e.g., silver, copper oxide) with outstanding antifungal activities and their mechanisms of action. It quantifies successes in agricultural applications demonstrating NPs’ potential in enhancing productivity and sustainability through nanocomposites, nanohybrid antifungals and nanobiosensors. Additionally, we address the environmental safety and scalability challenges, emphasizing the need for comprehensive field studies and the development of safe, effective nanoparticle delivery systems. The promising results underline NPs as a sustainable solution to combat phytopathogenic fungi, setting the stage for future innovations in agricultural disease management.